Efeitos da Magnitude de Consequências Individuais e Culturais sobre a Seleção de Culturantes de Autocontrole Ético - SILVA, Bruno Rodrigues da (Universidade Federal do Pará, 2019)
Metacontingencies relate to the contingent relationship between culturants (which includes interlocking behavioral contingencies and their aggregate products) and cultural consequences. Among the studies that have recently given empirical support to the concept of metacontingencies, are those that investigate the concurrence between individual and cultural contingencies under the notion of ethical self-control. Previous studies have evaluated the effect of increasing the magnitude of cultural consequence or individual consequence separately on cultural selection in concurrence contexts. However, no study has manipulated the magnitude of individual and cultural consequences together. The objective of this study was to evaluate the effect of the simultaneous manipulation of the magnitude of the individual and cultural consequences on the selection of culturants and individual responses of the participants in two microcultures. For this, a task involving a colored matrix of 10 rows (numbered from 1 to 10) and 10 columns (tagged with letters from "A" to "J") was used. The data collection was carried out with 2 groups (microcultures) of 3 college students. During the data collection with each microculture, each participant at a time selected a row from the matrix and received feedback from the experimenter about his or her choice. Choices on odd (impulsive) rows produced greater consequences for the individual while choices on even (self-controlled) rows produced lesser individual consequences, which, however, were correlated with the possibility of producing cultural consequences, when all 3 participants chose different color rows. During the experiment, the consequences varied so that as the magnitude of the individual impulsive consequence increased, the magnitude of the cultural consequence diminished and vice versa. The results indicated little influence of the variation of the magnitude of the consequences programmed in the experiment on the acquisition and maintenance of the culturantes and on the alteration of the pattern of the participants' choices in favor of the cultural or operant selection. New studies, with changes in the procedure, could better assess the influence of magnitude of consequences on the behavior of individuals in a group.